Policy, contextual matters and unintended outcomes: the English Baccalaureate (EBacc) and its impact on physical education in English secondary schools. Issue 6 (24th July 2019) - Maguire, Meg; Gewirtz, Sharon; Towers, Emma; Neumann, Eszter
ABSTRACT: This paper explores the implications of the English Baccalaureate (EBacc) for secondary school physical education (PE) departments and their teachers. The EBacc is a key performance measure that is published annually for each school, which privileges a particular set of traditional academic subjects, and in doing so, marginalises other subjects, including PE. At the same time as responding to this performance measure, secondary schools in England are required to respond to a wider set of policy reforms and innovations. This can sometimes result in overlap, collision and policy clash. For example, while PE is being sidelined and PE staffing reduced by the EBacc, there is national concern surrounding issues of fitness, health and well-being that schools are expected to address and which are often traditionally seen as the responsibility of PE departments. A reduction in their staffing will inevitably have consequences for their ability to respond in meaningful ways to such non-academic policy imperatives. Drawing on a study of the impact of recent curriculum and accountability reforms in English secondary schools (Neumann, E., Towers, E., Gewirtz, S., & Maguire, M. 2016. A curriculum for all? The effects of recent Key Stage 4 curriculum, assessment and accountability reforms on English secondary education . London: National Union of Teachers), this paper presents evidence of the marginalisation of PE and PE teachers' ensuing concerns about their job security. It also explores changes that have been made to the PE curriculum in an attempt to make the subject more academically demanding and considers what this means for PE teachers and their students. The authors conclude that if PE is going to contribute to broader fitness, health and wellbeing agendas, then there is an urgent need for a renewed debate – that reaches beyond PE communities and constituencies – about what PE is for, why it is important and how it can be better supported.